Dramatic Dramatic enhancement of the saturation magnetization of a sol-gel synthesized Y3Fe5O12 by a mechanical pressing process - Jang, Min-Sun; Roh, Im-Jun; Park, Jungmin; Kang, Chong-Yun; Choi, Won Jun; Baek, Seung-Hyub; Park, Sung Soo; Yoo, Jung-Woo; Lee, Ki-Suk (ELSEVIER SCIENCE SA, 2017)
We fabricated polycrystalline yttrium-iron-garnet (Y3Fe5O12, YIG) samples using the sol-gel synthesis method to develop an energy harvesting material based on the spin Seebeck effect. We confirmed that crystallization occurred during calcination at 850 degrees C and that only the polycrystalline YIG structure was formed. We found that a sintering process at 1400 degrees C not only increased the size of the YIG particles and the densification of their microstructure but also enhanced their saturation magnetization (M-s) and dramatically reduced their coercivity (H-c). A mechanical pressing process was carried out between the calcination and sintering treatments to prepare a free-standing YIG fillet sample. We found that M-s was enhanced by almost three times without an associated reduction in H-c. We found that mechanical pressing assists the oxidation reaction during the subsequent sintering process by increasing the surface energy and densification before the heat treatment. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: YTTRIUM-IRON-GARNET; SPIN; DRIVEN